Bibliometric Analysis of 3D Media Research Trends in Science Education from 2020 to 2025: A Literature Review - Rosita Mayanti, Alfiana Nur; Subali, Bambang (Journal of Biology Education, 2025)
Advances in digital technology have triggered a major transformation in the world of education, particularly through the use of technology-based learning media. One innovation that has attracted a lot of attention in recent years is the use of three-dimensional (3D) media in the science learning process. This literature review aims to (1) identify developments in research publications related to the use of 3D media in science education during the period 2020-2025; (2) analyse trends in 3D research in science education based on the number of publications, citations, authors, countries, and contributing journals; (3) Analyse the 3D tools used in the research, and (4) Provide an overview of opportunities and future research directions related to the application of 3D media in science education. The research method used was bibliometric analysis of a literature review assisted by Bibliloshiny software and Microsoft Excel for data tabulation. The database used was Scopus. The analysis resulted in a total of 50 documents analysed from the Scopus database. The results of the study show that (1) publications related to virtual reality in learning have increased, although they are not yet stable; (2) China and the United States have made the largest contributions related to 3D media, with the article with the highest number of citations being by Burley S.K. (2021). Burley S.K. is the author who has contributed the most to 3D media, with Applied Sciences (Switzerland) being the journal with the largest contribution; (3) The results show that 3D printing is the most discussed tool in research; (4) In addition, the study also shows that 3D media has the potential to be an innovation in learning in the future and continues to increase in its development.